The Safety and Feasibility of Laparoscopic Surgery for Very Low Rectal Cancer: A Retrospective Analysis Based on a Single Center’s Experience - Hyuk-Jun Chung (MDPI AG, 2021)
In this work we intend to validate the long-term oncologic outcomes for very low rectal cancer over the past 20 years and to determine whether laparoscopic procedures are useful options for very low rectal cancer. A total of 327 patients, who electively underwent laparoscopic rectal cancer surgery for a lesion within 5 cm from the anal verge, were enrolled in this study and their long-term outcomes were reviewed retrospectively. Of 327 patients, 70 patients underwent laparoscopic low anterior resection (LAR), 164 underwent laparoscopic abdominal transanal proctosigmoidocolectomy with coloanal anastomosis (LATA), and 93 underwent laparoscopic abdominoperineal resection (APR). The conversion rate was 1.22% (4/327). The overall postoperative morbidity rate was 26.30% (86/327). The 5-year disease free survival (DFS), 5-year overall survival (OS), and 3-year local recurrence (LR) were 64.3%, 79.7%, and 9.2%, respectively. The CRM involvement was a significant independent factor for DFS (p = 0.018) and OS (p = 0.042) in multivariate analysis. Laparoscopic APR showed poorer 5-year DFS (47.8%), 5-year OS (64.0%), and 3-year LR (17.6%) than laparoscopic LAR (74.1%, 86.4%, 1.9%) and laparoscopic LATA (69.2%, 83.6%, 9.2%). Laparoscopic procedures for very low rectal cancer including LAR, LATA, and APR could be good surgical options in selective patients with very low rectal cancer.